A cafeína exerce efeitos positivos sobre a memória tipo episódica em ratos adultos sem influenciar a sobrevivência neural no giro denteado - Macêdo, Priscila Tavares (2012)
The caffeine is a mild psychostimulant that has positive cognitive effects at low doses, while promotes detrimental effects on these processes at higher doses. The episodic-like memory can be evaluated in rodents through hippocampus-dependent tasks. The dentate gyrus is a hippocampal subregion in which neurogenesis occurs in adults, and it is believed that this process is related to the function of patterns separation, such as the identification of spatial and temporal patterns when discriminating events. Furthermore, neurogenesis is influenced spatial and contextual learning tasks. Our goal was to evaluate the performance of male Wistar rats in episodic-like tasks after acute or chronic caffeine treatment (15mg/kg or 30mg/kg). Moreover, we assessed the chronic effect of the caffeine treatment, as well as the influence of the hippocampus-dependent learning tasks, on the survival of new-born neurons at the beginning of treatment. For this purpose, we used BrdU to label the new cells generated in the dentate gyrus. Regarding the acute treatment, we found that the saline group presented a tendency to have better spatial and temporal discrimination than caffeine groups. The chronic caffeine group 15 mg/kg (low dose) showed the best discrimination of the temporal aspect of episodic-like memory, whereas the chronic caffeine group 30mg/kg (high dose) was able to discriminate temporal order, only in a condition of greater difficulty. Assessment of neurogenesis using immunohistochemistry for evaluating survival of new-born neurons generated in the dentate gyrus revealed no difference among groups of chronic treatment. Thus, the positive mnemonic effects of the chronic caffeine treatment were not related to neuronal survival. However, another plastic mechanism could explain the positive mnemonic effect, given that there was no improvement in the acute caffeine groups